Mothers’ Voices from the Kitchen: Understanding Daily Feeding Practices for Preschool Children in Rupandehi District of Nepal - Sharma, Prakash; Singh, Jitendra Kumar; Adhikari, Bishnu Kumar (Chhahari छहारी, 2026)
Background: Food practices are influenced by various interconnected factors such as individual preference, socio-cultural norms and marketing. Objective: This study explores how mothers perceive and manage daily food behaviors for their children. Methods: In this qualitative descriptive research semi-structured interviews were taken from purposely selected thirteen mothers of early childhood development children in Rupandehi district of Nepal, ensuring diversity in ethnicity, educational attainment, and maternal age. The response was coded manually by seeking recurring themes and grouping based on the type of foods. Result: The study revealed that mothers act as central agents in shaping children’s dietary routines, grounded in traditions, economic realities, health awareness, and evolving food environments. Meals like dal-bhat-tarkari were common, while breakfast and dinner practices varied depending on ethnic background, time constraints, and perceived child preferences. Despite low literacy among some mothers, there was a visible commitment to providing home-cooked and relatively nutritious food. Conclusion: The dietary practices of children are culturally rooted. There is a variation of food diversity in cultures. Culturally embedded caregiving, food choice of the children and availability of time to feed have critical role in balanced diet of children. These findings have implications for policy development in eating behavior of children in Nepal and similar socio-economic contexts.